Harnessing self-labeling enzymes for selective and concurrent A-to-I and C-to-U RNA base editing - Stroppel, Anna; Latifi, Ngadhnjim; Hanswillemenke, Alfred; Tasakis, Rafail Nikolaos; Papavasiliou, Nina; Stafforst, Thorsten (Nucleic acids research, 2021)
The SNAP-ADAR tool enables precise and efficient A-to-I RNA editing in a guideRNA-dependent manner by applying the self-labeling SNAP-tag enzyme to generate RNA-guided editases in cell culture. Here, we extend this platform by combining the SNAP-tagged tool with further effectors steered by the orthogonal HALO-tag. Due to their small size (ca. 2 kb), both effectors are readily integrated into one genomic locus. We demonstrate selective and concurrent recruitment of ADAR1 and ADAR2 deaminase activity for optimal editing with extended substrate scope and moderate global off-target effects. Furthermore, we combine the recruitment of ADAR1 and APOBEC1 deaminase activity to achieve selective and concurrent A-to-I and C-to-U RNA base editing of endogenous transcripts inside living cells, again with moderate global off-target effects. The platform should be readily transferable to further epitranscriptomic writers and erasers to manipulate epitranscriptomic marks in a programmable way with high molecular precision.
Gesehen am 22.11.2021